Incentive schemes and foreign investment in the industrialization of Malaysia - Karunaratne, N. D.; Abdullah, M. B. (University of California Press, 1978)
Post-independence, Malaysia has implemented policies to encourage private foreign investment (PFI) in the manufacturing industries through a plethora of incentive schemes (tax relief, pioneer status, investment tax credits, export incentives, locational incentives). The incentive schemes aimed to rectify the skewed nature of PFI which has concentrated in traditional extractive industries pre-independence, by encouraging diversification into manufacturing. However, the statistical analysis of survey results reveal that the incentive packages were ineffective and PFI was attracted to Malaysia and Singapore in order to gain a beachhead as a centre for regional distribution. Furthermore, the incentive schemes promoted capital-intensive industries and were located in developed regions with good infrastructure and financial services. Furthermore, the incentive schemes perpetuated unprofitable projects resulting in a drain on potential fiscal revenue. The study clearly reveals that whilst incentives such as free trade zones (FTZ) and tax-concessions promoted export oriented industries, overall the incentive packages were ineffective or even counterproductive. It appears that PFI is attracted more by non-incentive factors such as political stability and sound macroeconomic policies rather than tax-incentives. The need to reshape policies to attract the type of PFI that will generate employment and develop the rural hinterland needs to be addressed. In this context the prospects for regional cooperation among the ASEAN countries to counteract the 'concessions war' by harmonization of tax and incentive policies is moot.